Engineering of Biomaterials - dos Santos, Venina; Brandalise, Rosmary Nichele; Savaris, Michele; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book focuses on biomaterials of different forms used for medical implants. The authors introduce the characteristics and properties of biomaterials and then dedicate special chapters to metallic, ceramic, polymeric and composite biomaterials. Case studies on sterilization methods by biomaterials are also presented. Finally, the authors describe the degradation and effects of biomaterials in living tissue.
Keywords: Biomaterials; Metals; Biomedical engineering; Biomaterials; Metals and Alloys; Biomedical Engineering and Bioengineering